2013
DOI: 10.7314/apjcp.2013.14.6.3619
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Awareness and Perception of Tobacco Use Cessation Counseling among Dental Students in Four Asian Countries

Abstract: Background: The scientific evidence relating to the burden of oral diseases attributable to tobacco use has been reviewed and the need for a well-structured dental teaching program concentrating on oral cancer education and tobacco cessation interventions has been emphasized. The aim of our study was to evaluate the awareness of oral cancer and perception of tobacco use cessation counseling among dental students at all study levels in India, Saudi Arabia, the United Arab Emirates, and Yemen. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
6
30
1
1
Order By: Relevance
“…Furthermore suspicious lesions were positively related to lower levels of education (primary and intermediate) and the lowest income category (< 3000 SR/month) indicating that socio-economic factors may contribute to unhealthy lifestyles, using tobacco, and poor hygienic habits, which promote the occurrence of such lesions, and these factors were also reported in other studies (Shankar et al, 2010;Sujatha et al, 2012). This was further documented by the association of suspicious lesion with participants who reported to rarely brush their teeth Suspicious lesions were also positively related to Asian nationality and this may be explained by the high prevalence of tobacco chewing habits among Indians in the various ethnic groups as well as urban and rural inhabitants (Reddy and Shaik, 2008;Halawany, et al, 2013). Other studies also reported the prevalence of leukoplakia and other white lesions among elderly Chinese (22), and among selected Cambodian and Vietnamese populations (Ikeda, et al, 1995;Nair, et al, 1996).…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore suspicious lesions were positively related to lower levels of education (primary and intermediate) and the lowest income category (< 3000 SR/month) indicating that socio-economic factors may contribute to unhealthy lifestyles, using tobacco, and poor hygienic habits, which promote the occurrence of such lesions, and these factors were also reported in other studies (Shankar et al, 2010;Sujatha et al, 2012). This was further documented by the association of suspicious lesion with participants who reported to rarely brush their teeth Suspicious lesions were also positively related to Asian nationality and this may be explained by the high prevalence of tobacco chewing habits among Indians in the various ethnic groups as well as urban and rural inhabitants (Reddy and Shaik, 2008;Halawany, et al, 2013). Other studies also reported the prevalence of leukoplakia and other white lesions among elderly Chinese (22), and among selected Cambodian and Vietnamese populations (Ikeda, et al, 1995;Nair, et al, 1996).…”
Section: Discussionsupporting
confidence: 56%
“…Rahman et al (2013) showed an apparent lack of knowledge of oral cancer risk factors among dental students that may later result in a deficiency in integrating optimal oral cancer diagnostic procedures in their practices. Since tobacco use is a risk factor for oral cancer, Halawany et al (2013), showed that although more than 96% of the students surveyed recognized the association between oral cancer and cigarette smoking but tobacco use cessation counseling perception of students was poor.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts are required for the early detection and primary prevention of oral cancer among the community by the means of a variety of outreach programs related to education and awareness of oral cancer. Dental students may be particularly important in this context (Halawany et al, 2013).…”
Section: Introductionmentioning
confidence: 99%